Active summer carbon storage for winter persistence in trees at the cold alpine treeline. (12th March 2018) - Li, Mai-He; Jiang, Yong; Wang, Ao; Li, Xiaobin; Zhu, Wanze; Yan, Cai-Feng; Du, Zhong; Shi, Zheng; Lei, Jingpin; Schönbeck, Leonie; He, Peng; Yu, Fei-Hai; et al.
Abstract: The low-temperature limited alpine treeline is one of the most obvious boundaries in mountain landscapes. The question of whether resource limitation is the physiological mechanism for the formation of the alpine treeline is still waiting for conclusive evidence and answers. We therefore examined non-structural carbohydrates (NSC) and nitrogen (N) in treeline trees (TATs) and low-elevation trees (LETs) in both summer and winter in 11 alpine treeline cases ranging from subtropical monsoon to temperate continental climates across Eurasia. We found that tissue N concentration did not decrease with increasing elevation at the individual treeline level, but the mean root N concentration was lower in TATs than in LETs across treelines in summer. The TATs did not have lower tissue NSC concentrations than LETs in summer. However, the present study with multiple tree species across a large geographical scale, for the first time, revealed a common phenomenon that TATs had significantly lower NSC concentration in roots but not in the aboveground tissues than LETs in winter. Compared with LETs, TATs exhibited both a passive NSC storage in aboveground tissues in excess of carbon demand and an active starch storage in roots at the expense of growth reduction during the growing season. This starch accumulation disappeared in winter. Our results highlight some important aspects of the N and carbon physiology in relation to season in trees at their upper limits. Whether or to what extent the disadvantages of winter root NSC and summer root N level of TATs affect the growth of treeline trees and the alpine treeline formation needs to be further studied.